Horizontal transfer of domains in ssrA gene among Enterobacteriaceae. (9th June 2021) - Tamilmaran, Nagarajan; Sankaranarayanan, Ramamoorthy; Selvakumar A.S, Punitha; Munavar, M. Hussain
Abstract: The tmRNA (transfer messenger RNA), encoded by ssrA gene, is involved in rescuing of stalled ribosomes by a process called trans ‐translation. Additionally, regions of the ssrA gene (coding for tmRNA) were reported to serve as integration sites for various bacteriophages. Though variations in ssrA genes were reported, their functional relevance is less studied. In this study, we investigated the horizontal gene transfer (HGT) of ssrA among the members of Enterobacteriaceae. This was done by predicting recombination signals in ssrA gene (belonging to Enterobacteriaceae) using RDP5 (Recombination Detection Program 5). Our results revealed 7 recombination signals in ssrA gene belonging to different species. We further showed that the recombination signals were more in the domains present in the 3′ end than 5′ end of tmRNA. Of note, the mRNA region was reported in many recombination signals. Further, members belonging to genera Yersinia, Erwinia, Dickeya and Enterobacter were highly represented in the recombination signals. Sequence analysis revealed the presence of integration sites for different class of bacteriophages in ssrA gene. The locations of phage recognition sites are comparable with recombination signals. Taken together, our results revealed a diverse nature of HGT and recombination which possibly due to transduction mediated by phages. Abstract : tmRNA is a novel small RNA involved in various cellular processes. Many phages use the gene coding for tmRNA for genome integration. Thus, the gene coding for tmRNA is more prone for HGT and recombination. Thus, in this investigation, We intended to identify recombination signals in tmRNA belong to Enterobacteriaceae. An attempt was made to give plausible explanation behind the recombination using available information. ​